Lung recruitment improves the efficacy of intubation-surfactant-extubation treatment for respiratory distress syndrome in preterm neonates, a randomized controlled trial - Yong Yang; Wenkang Yan; Minyi Ruan; Lan Zhang; Jinzhen Su; Haohui Deng; Minxu Li (BMC, 2022)
Abstract Background Lung recruitment is a maneuver used to decrease the length of intubation in preterm neonates. This study aimed to compare the therapeutic efficacy of lung recruitment plus intubation-surfactant-extubation (INSURE) procedure and INSURE alone for the preterm neonates with respiratory distress syndrome. Methods From 2017 to 2019, 184 preterm neonates (gestational age 24-32 weeks) with respiratory distress syndrome were enrolled and randomized into the lung recruitment group receiving lung recruitment (25 cm H2O, 15 s) plus INSURE and the control group receiving INSURE only. The primary outcome was the need for mechanical ventilation (MV) within 72 h after extubation. The secondary outcomes included duration of MV, noninvasive ventilation, total oxygen therapy, hospitalization time, and complications. Results Compared to the control group, the lung recruitment group had a significantly lower proportion of preterm neonates requiring MV within 72 h after extubation (23% vs. 38%, P = 0.025) and pulmonary surfactant administration, as well as a shorter MV duration. There was no significant difference in the incidences of complications (all P > 0.05) and in-hospital mortality (2% vs. 4%, P = 0.4) between the lung recruitment group and control group. Multivariate logistic regression analysis demonstrated that the control group had a 2.17-time higher risk of requiring MV than the lung recruitment group (AOR: 2.17, 95% CI: 1.13-4.18; P = 0.021). Compared with infants with a normotensive mother, infants with a hypertensive mother have a 2.41-time higher risk of requiring MV (AOR: 2.41, 95% CI: 1.15-5.05; P = 0.020). Conclusion Lung recruitment plus INSURE can reduce the need for MV within 72 h after extubation and did not increase the incidence of complications and mortality. Trial registration Chinese Clinical Trial Registry ChiCTR1800020125 , retrospectively registered on December 15, 2018.